STATUS HUKUM JAMINAN PESAWAT DALAM PERKEMBANGAN OBJEK JAMINAN DI INDONESIA - Martin Ari Gunanta Sembiring (Faculty of Law, Universitas Pattimura, 2019)
Vacuity legal product of governing aircraft as an object of fiduciary guarantees raises legal problems regarding it’s status. Under the aircraft law the mortgage is guaranteed, but further arrangements regarding mortgage guarantees do not exist until now. The void of regulation has led to differing views about the guarantor institution that is authorized to guarantee aircraft. Apart from the guarantor institution, the types of financing and procedures for execution are difficult to determine because of the legal vacuum.